Liberalismo, democrazia, socialismo - Carmelo, Calabrò (Strumenti per la didattica e la ricerca, 2009)
In recent years the leader of "Giustizia e Libertà" has been the focus of a renewed and extensive attention. The author reconstructs the itinerary of Carlo Rosselli, conducting the theoretical analysis in the light of the complexity of the historic context. From the years of the Great War to the exile in France, intellectual meditation and political commitment are inextricably entwined threads in the career of the Florentine antifascist. In the attempt to pinpoint the key passages of this unquiet quest, the book traces the stages of an evolving thought. A thought that was matured through critical comparison with liberal theory and Marxist doctrine, found inspiration in English socialism and conceived opposition to the Fascist regime as the grounds for a project of progressive democracy.